Creating Competitive Advantage through Digital Innovation: Insights from Startupreneurs in E-Commerce - Gabriela Nicola; Rony Setiawan (Pandawan Sejahtera Indonesia, 2024)
Digital innovation has become a crucial factor in creating competitive advantage for startups in the e-commerce industry. In the fast-paced digital economy, startupreneurs must leverage technological advancements to differentiate themselves and ensure sustainable growth. This research aims to explore how digital innovation is utilized by startupreneurs in e-commerce to gain a competitive edge, focusing on the strategies that enhance market presence and customer loyalty. A mixed-method approach was adopted, combining surveys and in-depth interviews with e-commerce startupreneurs, along with a comprehensive literature review to provide a theoretical foundation. The findings indicate that startups implementing digital innovations such as automation, data analytics, and personalized customer experiences see significant improvements in customer satisfaction and operational efficiency. These innovations play a pivotal role in helping e-commerce startups maintain competitiveness in a saturated market. In conclusion, this study highlights the practical importance of adopting digital innovation for e-commerce startups and contributes to the theoretical understanding of how digital tools can drive entrepreneurial success in modern markets